Safety Risk Analysis in AHTS Ship Operations Using the HAZOP Method - Alfarabi, Ahfadz Zidan; Suwondo, Iie; Dahri, Mohammad; Rahayu, Trisnowati (Universitas Hang Tuah, 2026)
Occupational safety on board ships is a crucial aspect that must be fully considered, especially in high-risk Anchor Handling Tug Supply (AHTS) vessel activities. This study aims to conduct a safety risk assessment on AHTS vessel activities using the Hazard and Operability Study (HAZOP) method. The research method used is descriptive qualitative, which involves direct observation, interviews, and documentation analysis to obtain comprehensive data on potential hazards and operability in AHTS vessel activities. Some key findings include the identification of often overlooked potential hazards, such as adverse weather conditions, poorly maintained equipment, and non-compliance with safety procedures. Based on the HAZOP analysis used in this study, these risks will be categorized into three levels: low risk, moderate risk, and high risk. The analysis shows that most risks are at the moderate risk level, which requires a planned control approach and temporary measures to reduce the risks. Implementation of recommended mitigation measures, such as regular training on occupational safety, better equipment maintenance, and strict supervision of procedural compliance, can shift the risks from the moderate to low risk level. Effectively implementing the HAZOP method can improve occupational safety on AHTS vessels.